New Advances in Statistical Modeling and Applications - Pacheco, António; Santos, Rui; Oliveira, Maria do Rosário; Paulino, Carlos Daniel (Selected Papers of the Statistical Societies, 2014)
This volume presents selected papers from the XIXth Congress of the Portuguese Statistical Society, held in the town of Nazaré, Portugal, from September 28 to October 1, 2011. All contributions were selected after a thorough peer-review process. It covers a broad range of papers in the areas of statistical science, probability and stochastic processes, extremes and statistical applications.